2019
DOI: 10.3390/ijms20143544
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Levels of Protein Kinase Cs in Brain: Reduction of Endogenous Mechanisms of Neuroprotection

Abstract: Neurodegenerative diseases are among the leading causes of mortality and disability worldwide. However, current therapeutic approaches have failed to reach significant results in their prevention and cure. Protein Kinase Cs (PKCs) are kinases involved in the pathophysiology of neurodegenerative diseases, such as Alzheimer’s Disease (AD) and cerebral ischemia. Specifically ε, δ, and γPKC are associated with the endogenous mechanism of protection referred to as ischemic preconditioning (IPC). Existing modulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 116 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…The inhibition of PKC or Akt that accompanies neuronal death has been observed in the brain under excitotoxic conditions, and this excitotoxic brain damage also appears to be prevented by PKC or Akt activation. 47,48 In addition, PKC has been found to phosphorylate the C-terminal intracellular regulatory domain of the AMPA receptor subunit, including GluR2, 49 and this PKC-GluR2 axis is known to play a neuroprotective role in glutamate-induced neurotoxicity. 50 In our study, we found that the KA-induced decreases in the phosphorylation of the AMPA receptor subunit GluR2 and PKCα were significantly increased by eupafolin, implying that the PKC-GluR2 axis is also involved in the anticonvulsant and neuroprotective effects of eupafolin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The inhibition of PKC or Akt that accompanies neuronal death has been observed in the brain under excitotoxic conditions, and this excitotoxic brain damage also appears to be prevented by PKC or Akt activation. 47,48 In addition, PKC has been found to phosphorylate the C-terminal intracellular regulatory domain of the AMPA receptor subunit, including GluR2, 49 and this PKC-GluR2 axis is known to play a neuroprotective role in glutamate-induced neurotoxicity. 50 In our study, we found that the KA-induced decreases in the phosphorylation of the AMPA receptor subunit GluR2 and PKCα were significantly increased by eupafolin, implying that the PKC-GluR2 axis is also involved in the anticonvulsant and neuroprotective effects of eupafolin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Given that Prkcd is expressed in the hippocampus and dentate gyrus and can regulate ethanol’s effect on extrasynaptic GABA A receptors, CIEE might have upregulated Prkcd expression in the hippocampus of the aged rats, thereby altering extrasynaptic tonic GABAergic currents and in turn contributing to the impaired behavioral flexibility. Moreover, Prkcd had been implicated in AD . Increased PRKCD levels were found in brain tissues of patients with AD compared to those of individuals without the disease, and the inhibition of PRKCD expression was shown to reduce BACE1 expression and amyloid-β levels .…”
Section: Resultsmentioning
confidence: 99%
“…Neurodegenerative diseases are one of the leading causes of death and disability worldwide. PAK1 is involved in intracellular signaling pathways downstream of in-tegrins and receptor-type kinases and plays an important role in cytoskeleton dynam-ics, cell adhesion, migration, proliferation, apoptosis, mitosis, and vesicle-mediated transport processes as well as involving in the pathophysiology of neurodegenerative diseases, such as Alzheimer’s Disease (AD) and cerebral ischemia [ 61 ]. PAK1 expres-sion was altered with aging.…”
Section: Resultsmentioning
confidence: 99%